Motion-Guided Mechanical Toy Modeling - Zhu, Lifeng; Xu, Weiwei; Snyder, John; Liu, Yang; Wang, Guoping; Guo, Baining (ACM Transactions on Graphics (TOG) - Proceedings of ACM SIGGRAPH Asia 2012, 2012)
We introduce a new method to synthesize mechanical toys solely from the motion of their features. The designer specifies the geometry and a time-varying rotation and translation of each rigid feature component. Our algorithm automatically generates a mechanism assembly located in a box below the feature base that produces the specified motion. Parts in the assembly are selected from a parameterized set including belt-pulleys, gears, crank-sliders, quickreturns, and various cams (snail, ellipse, and double-ellipse). Positions and parameters for these parts are optimized to generate the specified motion, minimize a simple measure of complexity, and yield a well-distributed layout of parts over the driving axes. Our solution uses a special initialization procedure followed by simulated annealing to efficiently search the complex configuration space for an optimal assembly.